PENERAPAN PEMBELAJARAN VIRTUAL MOODLE BERBANTUAN GEOGEBRA UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR - Indri Lestari; Khotimah Khotimah; Tb. Sofwan Hadi (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2022)
This study aims to determine the increase in student learning independence by implementing Geogebra-assisted Moodle virtual learning. The method used is the experimental method with a one group pretest posttest research design. The research subjects were class VII students of SMP Negeri 6 Serang City. The data collection technique uses independent learning by distributing questionnaires before and after product trials during limited trials and field trials. An increase in learning independence is known by using the n-gain test to obtain an average result of 0.6 with moderate criteria during the limited test and field test